Comparison of several models to assess the effect of micromixing phenomena on the yield of complex chemical reactions in stirred tank - Ali Altway; Sugeng Winardi; M Rachimoellah (Jurnal Teknik Kimia Indonesia, 2004)
The effect of micromixing phenomena on the course of chemical reactions occuring in continuous stirred tank reactor was very important especially for fast reactions case. Previous workers have analyzed the effect using several models. The aim of this work is to make comparative study of several models to asses the effect of micro mixing phenomena on the course of two competitive fast parallel chemical reactions carried out in continuous stirred tank reactors. The reaction system investigated was the same as that studied by Baldyga (2001), neutralization of sodium hydroxide and hydrolysis of ethyl chloroacetate. Two closure approaches based on CFD available in FLUENT, Generalized Finite Rate Formulation (GFRF) and Probability Density Function (PDF), and a mechanistic model, Packet Diffusion Model, have been compared in assessing the effect of turbulent mixing on the yield of reaction. Baldyga's experimental data have been used to validate the computational results. The study concludes that a simple mechanistic model, Packet Diffusion Model, can predict fairly well (comparable in accuracy to the more sophisticated model such as PDF and GFRF model) the effect of micromixing phenomena on the course of parallel competitive chemical reactions in the continuous stirred tank reactor.Key Words : Micromixing, Continuous Stirred Tank Reactor, C.FD, PDM, GFRF, PDFAbstrakPengaruh fenomena micromixing terhadap berlangsungnya reaksi kimia yang terjadi di dalam reaktor kimia tangki berpengaduk menjadi sangat penting terutama untuk kasus reaksi-reaksi cepat. Beberapa penelitian terdahulu telah menganalisa secara teoritis pengaruh fenomena ini terhadap kinerja reaktor tangki teraduk menggunakan beberapa model. Tujuan penelitian ini adalah untuk membandingkan beberapa model untuk menganalisa pengaruh fenomena micromixing pada jalannya dua reaksi paralel kompetitif cepat yang terjadi di dalam reaktor alir tangki teraduk menggunakan beberapa model. Sistem reaktor yang diselidiki adalah sama dengan yang dipelajari Baldyga (2001), yaitu reaksi netralisasi sodium hidroksida dan hidrolisa ethyl chloroacetat. Dua pendekatan closure berbasis CFD yang tersedia pada FLUENT, yaitu Generalized Finite Rate Formulation (GFRF) dan Probability Density Function (PDF), dan suatu model mekanistik, yaitu Packet Diffusion Model, telah dibandingkan dalam menganalisa pengaruh pencampuran turbulen pada yield reaksi. Data eksperimen Baldyga telah digunakan untuk mengvalidasi hasil-hasil perhitungan. Penelitian ini menyimpulkan bahwa model mekanistik yang sederhana, yaitu Packet Diffusion Model, dapat memprediksi cukup baik, sebanding dari segi ketelitiannya dengan model berbasis CFD yang lebih rumit, pengaruh fenomena micromixing terhadap jalannya dua reaksi paralel kompetitif di dalam reaktor tangki teraduk.Kata Kunci : Micromixing, Reaktor Alir Tangki Teraduk, CFD, PDM, GFRF, PDF